Carpal Tunnel Syndrome and Associated Factors Among Workers in Blacksmithing Industry in Java, Indonesia - I Gede Maha Putra; Marsen Isbayuputra; Winnugroho Wiratman; Rakhmad Hidayat; Dewi Sumaryani Soemarko (The Indonesian Journal of Community and Occupational Medicine, 2025)
Introduction: Carpal Tunnel Syndrome (CTS) is one of the most common work-related musculoskeletal disorders, particularly in the informal sector such as traditional blacksmithing industries. Objective. This study aims to determine the prevalence and associated factors of CTS among blacksmith workers in Mekarmaju Village, Bandung Regency. Methods: Using a cross-sectional design, data were collected from 100 male workers through questionnaires, work observations, and physical examinations (Phalen and Tinel tests). Result:The results showed a CTS prevalence of 68%, with the majority of cases being bilateral. Bivariate analysis revealed several factors associated with CTS, including body mass index, age, dominant hand, and type of work. However, multivariate analysis identified only work duration (>3 years) as a significantly associated factor (aOR = 0.03; 95% CI: 0.01–0.92; p = 0.045), indicating that newer workers are more vulnerable to CTS. Conclusion: These findings highlight the importance of early ergonomic interventions and health screening at the beginning of employment to prevent CTS in the informal labor sector.